The Influence Of The Application Of Learning Strategies Model Elaboration Results Learn Aqeedah Akhlaq In MTs Mu'allimat College Cukir Jombang - Imam Muslih (EDUCATIO : Journal of Education, 2018)
Learning models of elaboration is to start learning the contents of the presentation on the general level of moving to a detailed level (elaborative sequence). By learning from the general to the particular pattern, giving students a simple description contained in the content frame (epitome) then develop into sub-sub material in more detail. Besides that, there are two stages of elaboration stimulate students' memory where the second elaboration stage as the consolidation of the student's abilities in the first stage of elaboration. Also students are encouraged to develop a sense of high social learning designed to implement cooperatively, it Allows students who are less intelligent can ask more intelligent students in the group (peer learning) .The purpose of this research are: 1) Describe the learning strategy elaboration on the models of morality in subjects aqeedah; 2) Describe the learning outcomes of subjects aqeedah morality; 3) Describe the effect of the application of learning strategies elaboration models of the learning outcomes of aqeedah morality in MTs-PM Cukir Jombang. This research is a quantitative research approach ex post facto. Conclusion: 1. Learning models of elaboration is to start learning the contents of the presentation on the general level of moving to a detailed level (elaborative sequence), giving students a simple description contained in the content frame (epitome) then develop into sub- sub material in more detail.2. The learning result is Obtained behavioral changes after studying the material learners demonstrated creed Akhlaq results.3 through the final test. There is a positive and significant influence between the Implementation of Learning Strategy Elaboration Of Learning Outcomes creed Akhlaq College Students at MTs Cukir Mu'alimat Jombang.